Effects of a mathematics game-based learning environment on primary school students' adaptive number knowledge. (January 2019) - Brezovszky, Boglárka; McMullen, Jake; Veermans, Koen; Hannula-Sormunen, Minna M.; Rodríguez-Aflecht, Gabriela; Pongsakdi, Nonmanut; Laakkonen, Eero; Lehtinen, Erno
Abstract: Developing adaptive expertise with arithmetic problem solving is a much desired aim of primary school mathematics education. However, there are very few practical tools for teachers that would aid reaching this complex mathematical learning goal. The aim of the present study was to test the effects of a game-based learning environment in supporting primary school students' adaptive number knowledge and related arithmetic skills. Participants were 1168 students in grades four, five, and six. Classes were randomized in two conditions: in the experimental group regular mathematics teaching was enriched with gameplay using the Number Navigation Game (NNG), and in the control group students continued according to their regular math curriculum. An experimental design with pre- and post-test was used to measure students' adaptive number knowledge, arithmetic fluency, and pre-algebra knowledge. Overall, results showed that the experimental group outperformed the control group on adaptive number knowledge and math fluency. Results showed varying effects of the training in different grade levels, with more pronounced improvement of students' adaptive number knowledge in grade five. Game performance was related to the experimental group's post-test scores even after controlling for pre-test scores and grade. Results suggest that the NNG is effective in enhancing different types of arithmetic skills and knowledge in different grades of primary school education and can provide teachers with a practical and flexible tool to extend their regular classroom practice. Highlights: Game-based intervention for training adaptive number knowledge was used. Results showed a positive impact on adaptive number knowledge. The intervention had varying effects across different grades. Game performance was related to the increase of math learning outcomes. Adaptive number knowledge can be enhanced by the Number Navigation Game.